(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2023)
Web service technology has gained a more important role in developing distributed applications and systems on the Internet. The rapid growth of published web services makes their discovery more and more difficult. Nowadays, most web service providers sign Services Level Agreement (SLA) contracts with their clients in order to guarantee the offered functionality of their services. This paper proposes an approach to monitor the Quality of Services (QoS) in web service according to Service Level Objectives (SLO) in SLA. Monitoring procedures are introduced to check variations in the pre-agreed metric values of SLAs. Then, the deviation between the actual quality and the acceptable quality level can be identified and analyzed. Finally, the weaknesses of the web service practices can be discovered and solved.